Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis). - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthan N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J.G.; White, Robert W.G.; Sladek, Rob (HAL CCSD, 2000)
International audience Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations ( Arctocephalus gazella and A. tropicalis ) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis . A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis , respectively. There was no geographical distribution of lineages observed within either species, although the respective F ST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis , the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella , there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvetøya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles ...